2020
DOI: 10.21203/rs.3.rs-66224/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Blockade of IDO-kynurenine-AhR pathway promotes cell apoptosis in carboxyamidotriazole-induced tumor cell dormancy-apoptosis oscillation

Abstract: Background: Some cancer cells may reshape their genetic make-up, adopt a special metabolism mode and undergo dormancy to endure drug attacks. Blocking survival signals in dormant cancer cells that survive a certain anticancer therapy and eradicating them while dormant may help prevent tumor recurrence and metastasis.Methods: Two colorectal cancer cell lines C26 and HCT116 were treated with carboxyamidotriazole. Sulforhodamine B assay and Ki67 staining were conducted to detect the cells proliferation response. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…This leads to cell dormancy-a state in which cells poorly proliferate and are highly resistant to pharmacological intervention (Figure 1). Shi et al showed that blocking IDO1/Kyn/AhR pathway restores a cell cycle and induced apoptosis of TRCs [109], thus may be a proper strategy in disease relapse prevention. Additionally, TRCs release Kyn which then upregulates PD-1 expression on CD8+ Tcells by AhR activation (Figure 4) [110].…”
Section: Ahr Agonists-carcinogenesis Modulatorsmentioning
confidence: 99%
“…This leads to cell dormancy-a state in which cells poorly proliferate and are highly resistant to pharmacological intervention (Figure 1). Shi et al showed that blocking IDO1/Kyn/AhR pathway restores a cell cycle and induced apoptosis of TRCs [109], thus may be a proper strategy in disease relapse prevention. Additionally, TRCs release Kyn which then upregulates PD-1 expression on CD8+ Tcells by AhR activation (Figure 4) [110].…”
Section: Ahr Agonists-carcinogenesis Modulatorsmentioning
confidence: 99%